Gender differences in rotation of the shank during single-legged drop landing and its relation to rotational muscle strength of the knee - Kiriyama, S.; Sato, H.; Takahira, N. (The American Journal of Sports Medicine, 2009)
Increased shank rotation during landing has been considered to be one of the factors for noncontact anterior cruciate ligament injuries in female athletes. There have been no known gender differences in rotational knee muscle strength, which is expected to inhibit exaggerated shank rotation.